ÖZEL OKUL ÖĞRETMENLERİ VE ÖĞRETİM YILINA HAZIRLIK ÖDENEĞİ - (:unkn) unknown (My University, 2014)
5580 sayılı Özel Eğitim Kurumları Kanunu özel okul öğretmenlerinin ücreti konusunda istisnai kurallar içermektedir. Buna göre, özel okul öğretmenlerine devlet okullarındaki emsallerinden daha düşük ücret ödenemez. Ayrıca işveren devlet okullardan çalışan öğretmenlere yapılan tüm ek ödemeleri özel okul öğretmenlerine de sağlamak zorundadır. Öğretim yılına hazırlık ödeneği, söz konusu ek ödemeler arasında yer almaktadır. Ne var ki Yargıtay 2012 yılında, özel okul öğretmenlerinin öğretim yılı hazırlık ödeneğinden yararlanamayacağına hükmetmiştir.

Law No. 5580 concerning Private Education Institutions contains exceptional rules regarding the wage of the private school teachers. Accordingly, the private school teachers can claim the minimum amount of the wage that is being payed to their counterparts working at the state schools. Moreover, the employer (private school owner) has the obligation to provide all the additional specific allocations to the teachers. Preparation subsidy for academic year is one of these additional specific allocations. Nonetheless, In 2012 the Supreme Court ruled that the the private school teachers can not benefit the preparation subsidy for academic year.
Private School Teachers and Prep aration Subsidy for Academic Year
Keywords: Temel Sağlık Hizmetleri; Eğitim, Eğitim Araştırmaları; Tarih